5x+7=3x+3

Simple and best practice solution for 5x+7=3x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+7=3x+3 equation:


Simplifying
5x + 7 = 3x + 3

Reorder the terms:
7 + 5x = 3x + 3

Reorder the terms:
7 + 5x = 3 + 3x

Solving
7 + 5x = 3 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
7 + 5x + -3x = 3 + 3x + -3x

Combine like terms: 5x + -3x = 2x
7 + 2x = 3 + 3x + -3x

Combine like terms: 3x + -3x = 0
7 + 2x = 3 + 0
7 + 2x = 3

Add '-7' to each side of the equation.
7 + -7 + 2x = 3 + -7

Combine like terms: 7 + -7 = 0
0 + 2x = 3 + -7
2x = 3 + -7

Combine like terms: 3 + -7 = -4
2x = -4

Divide each side by '2'.
x = -2

Simplifying
x = -2

See similar equations:

| 11x+5=15+10x | | 3x^4=360 | | f+3=15 | | 4x+3(x-1)=-2(x-3)+9 | | 2/5(x-4)=2x | | f-3=15 | | 2f+3=15 | | 2g=60+5g | | 7x=4x+18 | | 4*.25x-2=0 | | 2f-3=15 | | -2x+1+9x-5=7x-4 | | p+9=4p-12 | | (-(x-4)(x-4))=0 | | 8x-6+x-1=13 | | 3y=7+15 | | 8(k-3)=32 | | 4j-3j= | | (n+4)*9=72 | | 4s-13=15 | | (n-7)*3=12 | | 42x+3=43x | | (n+2)*5=20 | | 7x-1=3(x+2) | | 4a-1a=4 | | 4a-1a=4# | | 4-3(x+1)=10 | | 31x+4=128 | | -2(-x-4)=-2x+4 | | 9-3(2+y)=9 | | 8(4+y)=7(y-6) | | x+106=100 |

Equations solver categories